Reaksi saham perbankan terhadap penurunan BI rate April 2016 dan implikasinya terhadap strategi investasi: pengujian terhadap hipotesis pasar efisien - Triyaryati N; Kusumadewi NMW (Universitas Mercu Buana Yogyakarta, 2018)
Stagnation of BI Rate during year 2015 on 7.5% level, causing a profit growth deceleration and stock price compulsion in banking sector. BI rate and BI 7-Day Repo Rate policy announcement on April 21st 2016 is a new relevant information for banking sector in Indonesia. Because both are as an interest rate reference for determining deposit and landing interest rate, which directly related to banking sector profit and expenses. This study verify an abnormal return existence during the announcement, in order to observe the market ability to directly absorb the relevant information and reflected in the stock price of the banking sector. The procedures which run in this study is also to test the market efficiency theory in the semi strong form.This study indicate that during the observation period there is no existence of abnormal return, which is show that the market are directly absorb the new relevant information and reflected it in the stock prices. Thus the market indicate as semi strong efficient.Investor decision making implication refer to this study result is there will not be an optimal return for them if they applied an active investment strategy during this period.So, in this semi strong market efficiency situation, it is better for the investor not to apply the active investment strategy.